Time-related associations between local meteorological factors and dengue hemorrhagic fever hospital admissions in Iloilo, Philippines, 1990-1999 - Naragdao, Mary Ann F.; Guernsey, Judith R.; Weerasinghe, Swarna (Danyag :the UPV journal of humanities and social sciences, 2004)
"This study aimed to investigate the temporal trends and patterns of Dengue Hemorrhagic Fever (DHF) disease incidence in Iloilo, 1998, and to show associations, if any, o the specified local climate parameters. Daily cases of clinically confirmed DHF were obtained for the period 1990-1999 from the National Epidemic Sentinel Surveillance (NESS) of the Field Epidemiology Training Program of the Philippine Department of Health, Manila and the sentinel hospitals of Iloilo City. Daily climate date were obtained from local Iloilo weather station and Philippine Atmospheric, Geophysical and Astronomical Services Administration, Climatology and Agrometeorology Branch (PAGASA-CABI), Manila. Demographic data were obtained from the Iloilo Provincial Statistics Office. Sinusoidal curves fitted to the monthly standardized demographic vaviable were determined by maximum likelihood estimation using the Poisson regressions (SAS V.8.1). Results showed a total of 4586 DHF cases with highest admission count of 2076 in 1996 and lowest of 55 in 1999. Modal age of cases increased from 4 to 10 years over the decade. Seasonal trends were highly significant while peak numbers of cases were shown twice in 1991, 1992, 1996 and 1999. Poisson regression analysis of the combined age and gender groups showed that temperature (ß=0.2873) followed by rainfall (ß=0.0321) and relative humidiyt (ß=0.0247) were all significant independent predictor of DHF incidence, with temperature being the most significant. Climate factor I-month before admission is significantly related to incidence of DHF. Dengue programs and preventive measures should be initiated well before the rainy days particulary during aberrant climate conditions of El Niño. Disease surveillance programs of the Department of Health need coordination with the Weather monitoring station, and the Department of Environmental and Natural Resources."